THE ROLE OF E-COMMERCE BASED ON MARKETING 4.0 IN BUSINESS TRANSFORMATION - Arizal Hamizar; Mohammad H Holle; Jacsy Tubalawony (International Journal of Business, Law and Political Science, 2024)
This research investigates the role of e-commerce based on Marketing 4.0 in the transformation of businesses in the digital era. Through a theoretical study approach, the research aims to provide insights into the interplay between e-commerce, Marketing 4.0, and consumer behavior. The study begins by formulating clear research questions centered around the impact of e-commerce in the current digital landscape. Extensive literature review is conducted to identify relevant theoretical sources, including scholarly journals, books, articles, and publications related to e-commerce, Marketing 4.0, and consumer behavior. The findings of the study are synthesized into a coherent exposition, which offers a nuanced understanding of the role of e-commerce based on Marketing 4.0 in shaping business strategies and consumer behavior. Practical implications for companies seeking to develop effective marketing strategies in the dynamic digital landscape are discussed, along with suggestions for further research. Overall, this research contributes to the understanding of the evolving role of e-commerce and Marketing 4.0 in driving business transformation in the digital age.